2004
DOI: 10.1002/syn.20053
|View full text |Cite
|
Sign up to set email alerts
|

MDMA‐evoked changes in [11C]raclopride and [11C]NMSP binding in living pig brain

Abstract: Positron emission tomography (PET) studies with radiolabeled dopamine D2-like receptor ligands reveal d-amphetamine-evoked increases in the competition from endogenous dopamine. However, the corresponding effects of methylenedioxymethamphetamine (MDMA, "Ecstasy"), which releases catecholamines and also serotonin, are unknown. Using PET, we measured the binding potentials (pBs) of the benzamide [11C]raclopride and the butyrophenone N-[11C]methylspiperone ([11C]NMSP) in brain of living pigs first in a baseline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 58 publications
3
33
1
Order By: Relevance
“…Using cerebellum as reference region, average uptakes in ROIs were also analyzed by the Logan et al, SRTM (Gunn et al, 1998;Lammertsma and Hume, 1996) and ERliBiRD methods (Rosa-Neto et al, 2004). The ERLiBiRD method fits the following Equation…”
Section: Kinetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Using cerebellum as reference region, average uptakes in ROIs were also analyzed by the Logan et al, SRTM (Gunn et al, 1998;Lammertsma and Hume, 1996) and ERliBiRD methods (Rosa-Neto et al, 2004). The ERLiBiRD method fits the following Equation…”
Section: Kinetic Analysismentioning
confidence: 99%
“…To this end, we applied standard tissue reference methods to regions of interest (ROIs) and image voxels to obtain parametric estimates in the form of pB of [ 11 C]WAY. In addition, we compared the results to the results from the tissue reference method ERLiBiRD (Gjedde, 2003;Rosa-Neto et al, 2004). This method obtains estimates of extrapolation of specific uptakes ratios towards a predicted steady-state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minuzzi et al (2006), however, reported that several usual radioligands failed to bind to DAT in the pig brain, although they revealed the presence of DAT in rat, ferret, monkey and human brains. However, according to previous studies using a 11 C-raclopride paradigm, pigs possess functional DAT (Rosa-Neto et al, 2004). These discrepancies may be due to the aberrant binding properties of DAT in pigs compared with those in other species.…”
mentioning
confidence: 98%
“…Thanks to the development of methods for measuring cerebral uptake and metabolism of [ 18 F]fluoro-L-DOPA (FDOPA) (Danielsen et al, 1999 and 2001b), it is possible to analyse the activity of DOPA decarboxylase in living pig and apply this strategy to investigate the effect of neuroleptics (Danielsen et al, 2001a). Similarly, PET studies with [ 11 C]raclopride, a radioligand binding in competition with the endogenous dopamine, have been conducted to analyse the effect of psychoactive drugs such as amphetamine (Lind et al, 2005b), nicotine (Cumming et al, 2003), MDMA (Rosa-Neto et al, 2004b) and lysergic acid diethylamide (Minuzzi et al, 2005). It has been shown that these psychoactive agents reduced the availability of [ 11 C]raclopride binding sites for dopamine D(2,3) receptors in the striatum of Gö ttingen minipigs.…”
mentioning
confidence: 99%